An evaluation on the implementation of portfolio assessment in an English subject BEL120 (Consolidating Language Skills) / Hanis Kamarudin - Kamarudin, Hanis (2010)
Universiti Teknologi Mara (UiTM) has a branch campus in every state in Malaysia. Faculty of Business Management is one of the faculties in Universiti Teknologi Mara (UiTM) Kelantan and one of the programmes offered is the three-year Diploma in Business Studies programme. In order to ensure that the students are able to use proper English in studying and in working environment later, English language is offered as a compulsory subject beginning from Consolidating Language Skills or BEL 120. Portfolio assessment was introduced recently with a view to improving the assessment quality especially in essay writing and help lecturers and students improve teaching and learning respectively. This study was carried out to investigate the implementation of portfolio assessment in BEL 120 among the Part 1 Diploma in Business Studies students and English lecturers at UiTM Kelantan. The process of collecting the data was done by means of questionnaire to students and interview questions to the lecturers. The respondents for this study were thirty five students and seven BEL120 English lecturers. Among the main questions to be answered are: Do the students understand on the purpose of the implementation of portfolio assessment? Do the students use self-reflection during the writing in portfolio tasks? What kind of feedbacks that the students feel is important from lecturers in portfolio assessment? What are the students' opinions on the use of portfolio assessment? How much do the lecturers understand on the main purpose of using portfolio assessment? What types of feedbacks that the lecturers give to the students on the writing portfolio tasks? How often do the lecturers give the feedbacks to students on the writing portfolio tasks? What are the lecturers' opinions on the effectiveness of portfolio assessment? Based on the responses from the students, although the lecturers have given enough explanation on the purpose of portfolio assessment, a large number of them did not have much understanding regarding it. However, they indicated portfolio assessment has helped them to do self-reflection and the positive feedbacks from lecturers were important to improve their learning. The interview with the lecturers showed that they were aware on the main purpose of using portfolio assessment. The lecturers did give both positive and negative type of feedbacks to the students and gave sufficient feedbacks on the students' work whenever needed. The feedbacks were given all the time to ensure that the students will reflect on their strengths and weaknesses in the written task. The results have shown that both students and lecturers gave positive perspectives on portfolio assessment. It can be concluded that the use of portfolio assessment in BEL120 subject was effective and useful. As this study only involved 35 students and 7 English lecturers, it is recommended that a study be carried out on a larger sample to get a better perspective on the implementation of portfolio assessment in BEL120 subject. For future research, similar study should be done in portfolio assessment involving other language components such as reading.